2020
DOI: 10.1096/fj.202001641r
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin receptor 1 ameliorates insulin resistance in skeletal muscle

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As shown in Figure , 2 μg/mL collagen‐stimulated platelet aggregation and rate of aggregation were significantly impaired by the addition of 50 nM IL32. By contrast, 2 µg/mL collagen‐stimulated platelet aggregation was not affected by the addition of PROK2 at a concentration of 10 nM ( Figure ), representing ~ 10 to 50‐fold the half‐maximal effective concentration of this cytokine in in vitro assays 31,32 . Moreover, the addition of PROK2 alone to washed platelets did not lead to appreciable aggregation ( Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure , 2 μg/mL collagen‐stimulated platelet aggregation and rate of aggregation were significantly impaired by the addition of 50 nM IL32. By contrast, 2 µg/mL collagen‐stimulated platelet aggregation was not affected by the addition of PROK2 at a concentration of 10 nM ( Figure ), representing ~ 10 to 50‐fold the half‐maximal effective concentration of this cytokine in in vitro assays 31,32 . Moreover, the addition of PROK2 alone to washed platelets did not lead to appreciable aggregation ( Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…AVPR1A expression is increased in failing hearts, and overexpression of AVPR1A in a mouse model has been shown to impair cardiac function (51). Other GPCRs with remarkable expression profiles include orphan GPCR (GPR35) (52), Prokineticin Receptor 1 (PROKR1) (53), LGR4 (54)(55), and Adhesion G Protein-Coupled Receptor F5 (AD-GRF5) (56). Previous studies have suggested that these GPCRs may play a critical role in controlling adipocyte biology and systemic energy homeostasis but more work is needed for a detailed understanding of their functional significance in adipose tissue metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is the primary and largest site for modulating normal glucose concentrations in the postprandial state in humans. More than 80% of glucose uptake activity is mainly regulated in skeletal muscle under euglycemic hyperinsulinemic conditions [58,59]. In skeletal muscle, insulin binds to the insulin receptor, which leads to activation of PI3K and an increase in the level of intracellular PIP 3 .…”
Section: Role Of Pi3k/akt In Muscle Tissuementioning
confidence: 99%
“…In skeletal muscle, insulin binds to the insulin receptor, which leads to activation of PI3K and an increase in the level of intracellular PIP 3 . The PIP 3 activates AKT2 at the plasma membrane, which is necessary for subsequent glucose uptake into the skeletal muscle through GLUT4 membrane translocation [59,60]. Incorporated glucose is converted to glycogen for storage or enters the glycolytic pathway where it is oxidized for energy production [61].…”
Section: Role Of Pi3k/akt In Muscle Tissuementioning
confidence: 99%